Effect of N-acetylcysteine inhalation on ventilator-associated pneumonia caused by biofilm in endotracheal tubes - Qu, D (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2016)
OBJECTIVE: To observe the formation of the biofilm in endotracheal tubes, the characteristics of etiology, drug resistance and effect on the biofilm and ventilator-associated pneumonia (VAP) of inhaled N-acetylcysteine (NAC)